The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2007
DOI: 10.1159/000110744
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Accuracy of Cytokine Levels (TNF-α, IL-2 and IFN-γ) in Bronchoalveolar Lavage Fluid of Smear-Negative Pulmonary Tuberculosis Patients

Abstract: Background: The determination of cytokine concentrations in serum and bronchoalveolar lavage fluid (BALF) may contribute to the diagnosis of tuberculosis (TB) since cytokines have been ascribed an important role in TB pathogenesis. Objective: To assess the diagnostic accuracy of TNF-α, IFN-γ and IL-2 levels in serum and BALF of smear-negative pulmonary TB patients. Method: BALF was obtained from the affected lobe in patients with smear-negative TB or other pulmonary diseases (OPD), and from the right middle lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 52 publications
1
15
0
Order By: Relevance
“…These results are in agreement with other published results for IL-10 [10,11] and for TNF-α [12,13,14]. In contrast, IFN-γ and IL-12 levels were not different between healthy controls and TB patients.…”
Section: Discussionsupporting
confidence: 93%
“…These results are in agreement with other published results for IL-10 [10,11] and for TNF-α [12,13,14]. In contrast, IFN-γ and IL-12 levels were not different between healthy controls and TB patients.…”
Section: Discussionsupporting
confidence: 93%
“…1). At that time, numbers ofMtb in the lung of all mice had increased again up to 1.4x10 3 (range 1.0-6.8x10 3 ) , whereas in lout of 4 mice bacterial numbers in the spleen and liver had increased to numbers not significantly different from the untreated controls.…”
Section: Efficacy Ofanti-tuberculosis Drugsmentioning
confidence: 85%
“…The role of cytokines in the host defence during TB was demonstrated in various studies in TB patients, showing levels of IFN-y, TNF-a, IL-4, IL-6 and IL-IO in serum, and BAL fluid as well as in pleural fluid. It is not clear whether these changes in cytokine expression are related to the infection progression and therapy response, and (if so) could possibly be useful markers (3)(4)(5)(6)(7). Monitoring cytokine levels in BAL fluid is hindered by the fact that the collection of BAL fluid from patients is an invasive procedure and is susceptible to inter-procedure variations.…”
Section: Discussionmentioning
confidence: 99%
“…However, IFN- γ assays using both pleural effusions [22] and peritoneal ascites [23] are considerably expensive, which may render this method less clinically useful and practical. Küpeli et al (2008) investigated a less expensive method of testing for cytokines as diagnostic biomarkers of Tb, using serum and bronchoalveolar lavage fluid (BALF) [24]. This study found a TNF- α cutoff of 17.6 pg/mL in serum and BALF (sensitivity: 73%; specificity: 76%) for distinguishing patients with smear-negative Tb from healthy subjects.…”
Section: Role Of Cytokines and Their Clinical Cutoffs In Infectionmentioning
confidence: 99%